Low-Level Light Therapy Protects Red Blood Cells Against Oxidative Stress and Hemolysis During Extracorporeal Circulation - Walski, Tomasz; Drohomirecka, Anna; Bujok, Jolanta; Czerski, Albert; Wąż, Grzegorz; Trochanowska-Pauk, Natalia; Gorczykowski, Michał; Cichoń, Romuald; Komorowska, Małgorzata (Frontiers in Physiology, 2018)
INTRODUCTION An activation of non-specific inflammatory response, coagulation disorder, and blood morphotic elements damage are the main side effects of the extracorporeal circulation (ECC). Red-to-near-infrared (R/NIR) radiation is thought to be capable of stabilizing red blood cell (RBC) membrane through increasing its resistance to destructive factors. We focused on the development of a method using low-level light therapy (LLLT) in the spectral range of R/NIR which could reduce blood trauma caused by the heart-lung machine during surgery. METHODS R/NIR emitter was adjusted in terms of geometry and optics to ECC circuit. The method of extracorporeal blood photobiomodulation was tested during in vivo experiments in an animal, porcine model (1 hour of ECC plus 23 hours of animal observation). Twenty four sows weighing 90-100 kg were divided into two equal groups: control one and LLLT. Blood samples were taken during the experiment to determine changes in blood morphology (red blood cell (RBC) and white blood cell (WBC) counts, haemoglobin (Hgb)), indicators of haemolysis (plasma free haemoglobin (PFHgb), serum bilirubin concentration, serum lactate dehydrogenase (LDH) activity), and oxidative stress markers (thiobarbituric acid reactive substances (TBARS) concentration, total antioxidant capacity (TAC)). RESULTS In the control group, a rapid systemic decrease in WBC count during ECC was accompanied by a significant increase in RBC membrane lipids peroxidation, while in the LLLT group the number of WBC and TBARS concentration both remained relatively constant, indicating limitation of the inflammatory process. These results were consistent with the change in the haemolysis markers like PFHgb, LDH and serum bilirubin concentration, which were significantly reduced in LLLT group. No differences in TAC, RBC count, Hgb concentration were detected. CONCLUSION We presented the applicability of the low-level light therapy with R/NIR radiation to blood trauma reduction during extracorporeal circulation.